Mental health professional perception of the embracement towards psychoactive substance user in CAPSad - Salles, Daiane Bernardoni; Silva, Meire Luci da [UNESP] (Cuba Editora, 2017)
Introduction: Adherence to chemical dependency treatment is still a great challenge for both, users and health care professionals. Currently, public healthcare policy is a tool to assist in the development of a humanized care model, which advocates for the practice of user inclusion. Objective: Investigate the perception of professionals who work in the mental health field, to understand the inclusion offered to users of psychoactive substances in Psychosocial Care Centers for alcohol and drug users (CAPSad). Method: A descriptive and exploratory study conducted at the CAPSad in Sao Paulo. Active professionals in the mental health field working at the CAPSad participated in the present study. For data collection a semi-structured questionnaire was used with 27 self-report questions, 15 closed questions, analyzed through statistics and 12 open questions, with speech analysis. Results: The questionnaires of six professionals with a mean of 14.3 years working at the CAPSad, revealed that they had no prior training about inclusion. Five participants responded that they carried out inclusion in the presence of the family, four responded without the presence of family and just one responded according to user choice (each participant could choose more than one option). The results show ambiguity regarding the concept of user inclusion, as all reported that inclusion hampers user reception, qualified listening, guidance and making necessary referrals. Conclusion: The need to create formal spaces for knowledge exchange, case discussion, and encourage professional training, promoting the identity of the service and improving user adherence to treatment was highlighted.
Keywords: Substance-Related Disorders; User Inclusion; Mental Health Service